XUV and soft X-ray laser radiation from nickel-like lanthanide - Abdelaziz, Wessameldin S.; Hamed, Hamed Mahmoud; Farrag, Azza Abdel Hakim (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Atomic structure data and effective collision strengths for 1s2 2s2 2p6 3s2 3p6 3d10 and 54 fine-structure levels contained in the configurations 1s2 2s2 2p6 3s2 3p6 3d9 4l (l = s, p, d, f) for the nickel-like La ion have been investigated. These data are used in the determination of the reduced population for the 55 fine structure levels over a wide range of electron densities (from 1020 to 1022) and at various electron plasma temperatures. The gain coefficients for those transitions with positive population inversion factor are determined and plotted against the electron density.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 971-978
Keywords: optyka; XUV; soft X-ray; laser radiation; population inversion; gain coefficient